2006
DOI: 10.1016/j.intcom.2005.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The lonesome cowboy: A study of the usability designer role in systems development

Abstract: This paper reports on an evaluation of the usability designer role as applied in two Swedish systems development organisations. The role was initially defined by us, but evolved in these two organisations. We conducted interviews with usability designers, project managers and a user representative. Our main research question was whether or not the introduction of a usability designer has been successful in terms of changes in the systems development process and the impact the role has had on products, projects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 18 publications
2
57
0
Order By: Relevance
“…In these cases data collection methods are usually questionnaires (Rauch and Wilson, 1995;Vredenburg et al, 2002b;Venturi and Troost, 2004;Ji and Yun, 2006), interviews (Bekker, 1995;Borgholm and Madsen, 1999;Boivie et al, 2003;Boivie et al, 2006;Bruno and Dick, 2007), or a combination of both (Rosenbaum et al, 2000;Gulliksen et al, 2006;Neumann et al, 2009). Informants are mostly usability specialists and interaction designers, and the focus is usually not so much on the product development process and team as a whole, but on usability-related activities and usability departments.…”
Section: Studies Of Usability In Practicementioning
confidence: 99%
“…In these cases data collection methods are usually questionnaires (Rauch and Wilson, 1995;Vredenburg et al, 2002b;Venturi and Troost, 2004;Ji and Yun, 2006), interviews (Bekker, 1995;Borgholm and Madsen, 1999;Boivie et al, 2003;Boivie et al, 2006;Bruno and Dick, 2007), or a combination of both (Rosenbaum et al, 2000;Gulliksen et al, 2006;Neumann et al, 2009). Informants are mostly usability specialists and interaction designers, and the focus is usually not so much on the product development process and team as a whole, but on usability-related activities and usability departments.…”
Section: Studies Of Usability In Practicementioning
confidence: 99%
“…The data showed that the informative, consultative, participative and designer roles were all adopted by the usability specialists in the case project [in line with e.g. 3,13,15,16]. The usability specialists were providing information about users based on their empirical work with children and on their general state-of-the-art HCI knowledge, as well as offering both empirical user feedback and feedback based on their expert evaluations [see 15].…”
Section: Discussionmentioning
confidence: 99%
“…Gulliksen and his research group have reported numerous studies, mostly concerning public authorities in Sweden [e.g. 3,12,13], while Iivari has analyzed usability specialists work practices in product development in Finland [15,16]. These are qualitative inquiries on the matter, but there is also some survey research carried out [6,12,37] 26,27], reporting on usability specialists' ways of working when face-to-face contact is impossible.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations